The butterfly alphabet book - Cassie, Brian, 1953-; Pallotta, Jerry; Astrella, Mark (Watertown, MA : Charlesbridge, 1995)
Introduces butterflies from A to Z, describing their distinctive features while highlighting each letter of the alphabet.
Keywords: Butterflies -- Juvenile literature; English language -- Alphabet -- Juvenile literature; Butterflies; Alphabet; Butterflies; Alphabet